Urban mobility with a focus on gender: The case of a middle-income Latin American city - Olivieri, Cecilia; Fageda, Xavier (Journal of Transport Geography, 2021)
This study analyzes gender differences in travel patterns for the Metropolitan Area of Montevideo, Uruguay. By applying multilevel regression models, it provides estimates of the impact of individual and contextual factors on travel behavior. The paper's findings lend support to the household responsibility hypothesis, which claims that women's travel patterns are affected by the type of household in which they live and the consequent responsibilities or roles they assume. Furthermore, gender differences in travel patterns are reinforced across census tracts. The results indicate that policy makers need to consider gender differences when seeking to enhance urban planning decisions. © 2021 Elsevier Ltd
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; discipline; déplacements urbains; environnement; géographie; géographie urbaine; projet charge mentale; périodes historiques; régions géographiques; sciences humaines; thématiques; travail; uruguay

Rethinking social reproduction in the time of COVID-19 - Dattani, Kavita (The Journal of Australian Political Economy, 2020)
Keywords: 2000 à aujourd'hui; 2010-2019; 2020-2029; care; covid-19; discipline; genre; géographie; périodes historiques; ressource en ligne; sciences humaines; thématiques; travail; travail domestique; violences

The Routledge handbook of gender and violence - Lombard, Nancy (Routledge, 2018)
The Routledge Handbook of Gender and Violence provides both a comprehensive and authoritative state-of-the-art overview of the latest research in the field of gender and violence. Each of the 23 specially commissioned chapters develops and summarises their key issue or debate including rape, stalking, online harassment, domestic abuse, FGM, trafficking and prostitution in relation to gender and violence. They study violence against women, but also look at male victims and perpetrators as well as gay, lesbian and transgender violence. The interdisciplinary nature of the subject area is highlighted, with authors spanning criminology, social policy, sociology, geography, health, media and law, alongside activists and members of statutory and third sector organisations. The diversity of perspectives all highlight that gendered violence is both an age-old and continuing social problem. By drawing together leading scholars this handbook provides an up-to-the-minute snapshot of current scholarship as well as signposting several fruitful avenues for future research. This book is both an invaluable resource for scholars and an indispensable teaching tool for use in the classroom and will be os interest to students, academics, social workers and other professionals working to end gender-based violence.
Keywords: approches et analyses; communication; cours; criminologie; discipline; droit; géographie; justice sociale; outils; ouvrages de références; premier cycle; rapports sociaux de sexe; ressource en ligne; santé; science politique et droit; sciences humaines; sex1911; sexualité; sociologie; sofia; thématiques; travail; violences

Geography and gender: Feminism and a feeling of justice - Wright, Melissa W. (Progress in Human Geography, 2010)
The recent emphasis on emotional geographies has turned critical attention to the connections linking affect and social justice. It is hard to imagine this ‘emotional turn’ in the field without much of the ground having been laid by feminist challenges to epistemology, objectivity, rationality, to the gendering of knowledge and the conceptualization of human embodiment, psychic life, subjectivity, and political agency, all in relation to power so often substantiated around a belief that the public and the private are discrete and oppositional domains necessary for organizing social, economic, and political life. In this report, I address the following questions. How can feminist and emotional geography tighten their connections, fuel their shared passions and generate a synergy of scholarship oriented toward activism and progressive change? How can geographies of feeling broaden the path for justice that feminism endeavors to plow? In doing so, I continue my emphasis on research that grounds theoretical discussion with research conducted in activist projects conducted in the name of social justice. I do so as a matter of my own emotional investments – I firmly believe that scholarship must engage with the ways in which people beyond the academy wrestle with the concepts in their daily lives that scholars contemplate, sharpen, and circulate through academic production. So the debates that we scholars so often have with ourselves over the finer points of theory reveal, in my view, their greater significance when they provide tools useful for people who seek to create kinder and more compassionate worlds. Thus, I highlight the scholarship that creates toolkits out of feminist scholarship, emotional geographies, and research on social justice.
Keywords: approches et analyses; care; discipline; genre; géographie; justice sociale; militance; ressource en ligne; sciences humaines; thématiques; travail; travail du care; émotions

«Je pensais que je pourrais avoir une relation plus egalitaire avec un Europeen.» Le rôle du genre et des imaginaires geographiques dans la migration des femmes - Riaño, Yvonne; Baghdadi, Nadia (Nouvelles Questions Féministes, 2007)
Le nombre de femmes migrant vers la Suisse en provenance de pays extérieurs à l'Union européenne a considérablement augmenté ces dernières années. La féminisation de la migration a été conceptualisée dans la littérature comme une conséquence des forces économiques mondiales et comme la seule option pour les femmes des pays à faible revenu pour résoudre leurs besoins matériels. Cet article soutient que cette perspective est insuffisante pour expliquer la migration féminine. Sur la base d'une analyse qualitative des récits de vie de vingt femmes d'Amérique latine, d'Europe du Sud-Est et du Moyen-Orient, nous concluons que de nombreux facteurs autres que les difficultés économiques influencent les décisions des femmes de migrer. En particulier, le désir d'atteindre l'égalité des sexes dans la société au sens large et au niveau du ménage semble être une forte motivation à la migration. Les images positives de l'Europe, des Européens et des relations de genre en Europe favorisent des pays comme la Suisse comme destination de migration. Nous concluons que lorsque les femmes traversent les frontières, elles construisent et reconstruisent le genre, et que le genre façonne leurs schémas migratoires.
Keywords: cours; discipline; environnement; europe; femmes immigrantes; géographie; géographie du genre; récits de vie; régions géographiques; sciences humaines; soc1061; sociologie; suisse; thématiques; travail